2014
DOI: 10.1007/s10865-014-9558-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of sun protection behaviors among U.S. Hispanic adults

Abstract: The incidence of skin cancer among U.S. Hispanics increased 1.3% annually from 1992 to 2008. However, little research has focused on skin cancer prevention among the rapidly growing Hispanic population. In this study, we examined theory-driven, psychosocial correlates of sun protection behaviors in a population-based sample of 787 Hispanic adults (49.6% female, mean age = 41.0 years) residing in five southern or western U.S. states. Participants completed an English- or Spanish-language online survey in Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
6
31
0
Order By: Relevance
“…One study reported a midrange score in terms of skin cancer worry in Hispanics. Another study found that perceived skin cancer severity was associated with incidence of total body examination (i.e., a head-to-toe examination of the skin performed by a physician used to identify suspicious growths that may be cancer or growths that may develop into skin), but not with incidence of skin self-examination (i.e., a head-to-toe examination of the skin performed by the individual, not a physician) [30, 31]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study reported a midrange score in terms of skin cancer worry in Hispanics. Another study found that perceived skin cancer severity was associated with incidence of total body examination (i.e., a head-to-toe examination of the skin performed by a physician used to identify suspicious growths that may be cancer or growths that may develop into skin), but not with incidence of skin self-examination (i.e., a head-to-toe examination of the skin performed by the individual, not a physician) [30, 31]. …”
Section: Resultsmentioning
confidence: 99%
“…A third study also found lower perception of skin cancer risk when Hispanics were compared with whites but the difference was not significant when participants were asked to compare their own likelihood of getting skin cancer compared with the risk of an average person of the same age [29]. Two studies reported similar scores on their skin cancer risk and photoaging (changes in skin appearance induced by sun exposure) concern measures but used different scales for the scores [30, 34]. Participants were inclined to not agree or disagree (midrange score) with the following statement: “The natural color of my skin protects me from the sun” [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a degree of skin cancer fatalism exists within this age cohort. 16 Thus, since the primary motivation for UV exposure in young adults is to obtain a suntan, and the primary motive for sun tanning is appearance enhancement, it is reasoned that public health campaigns that highlight the negative effects of sun exposure on appearance might be more effective than those emphasising health risks.…”
Section: Introductionmentioning
confidence: 99%